(untitled) (Universal International Scientific Journal, 2026)
This article explores an innovative methodology for independent study of English for pharmacy students. This method is aimed at solving the problems of selecting educational materials and consolidating acquired knowledge that pharmacy students face in independent study of English. This method consists of two stages, which include visual information acquisition via YouTube and interactive reinforcement using generative artificial intelligence. This not only increases the effectiveness of language learning, but also helps the student develop critical thinking and consolidate his knowledge.